(untitled) (Denmark, 1995)
It is offered as a resource book providing guidance for people working with development and change, whether or not Danida - or any other donor - is involved.
Quản lý tài nguyên thiên nhiên và suy nghĩ hệ thống
Keywords: Đề án phát triển kinh tế,Economic development projects; Kế hoạch,Planning